Policy on Implementation of Bank Indonesia Circular Letter No. 14/7/Dpbs of 2012 concerning Regulation of Qardh Backed by Gold at Bank Syariah Mandiri KFO Imam Bonjol Medan (Pre Merger of PT Bank Syariah Indonesia) - Mutiara Minsih; Yusniar Lubis; Rudi Salam Sinaga (Budapest International Research and Critics University, 2021)
Bank Indonesia Circular Letter No.14/7/DPbS dated February 29, 2012 regarding Qardh Backed by Gold Products for Sharia Banks and Sharia Business Units explains the guidelines and operating limits for sharia gold pawn/rahn products in Indonesia. With the issuance of this circular, every Islamic bank including Bank Syariah Mandiri KFO Imam Bonjol Medan must be able to implement policies in accordance with the provisions of Bank Indonesia. This study aims to determine and explain how the implementation of gold-backed qardh products at Bank Syariah Mandiri KFO Imam Bonjol Medan after the issuance of Bank Indonesia Circular Letter No. 14/7/DPbS. This study also aims to determine the impact of potential risks that arise on gold-backed qardh products after the issuance of Bank Indonesia Circular Letter No. 14/7/DPbS. This research is a qualitative descriptive analysis research conducted at Bank Syariah Mandiri KFO Imam Bonjol Medan which is located at Jl. Imam Bonjol, No. 7. Medan City. Based on the results obtained in this study, it can be seen that in general, the implementation policies applied by Bank Syariah Mandiri KFO Imam Bonjol Medan are in accordance with the rules contained in Bank Indonesia Circular Letter No. 14/7/DPbS. Such as determining the category of use, use of contracts, delivery of information, amount and term of financing, and FTV. However, there are two aspects that are still not appropriate, including the status of gold ownership and the imposition of fees that are not in accordance with the rules set by Bank Indonesia. In addition, it is also known that in gold-backed qardh products there are several types of risks contained in them, including: market risk, credit risk, liquidity risk and operational risk.